Holoenzyme structures of endothelial nitric oxide synthase - an allosteric role for calmodulin in pivoting the FMN domain for electron transfer - Volkmann, Niels; Martásek, Pavel; Roman, Linda J; Xu, Xiao-Ping; Page, Christopher; Swift, Mark; Hanein, Dorit; Masters, Bettie Sue (Journal of structural biology, 2014)
While the three-dimensional structures of heme- and flavin-binding domains of the NOS isoforms have been determined, the structures of the holoenzymes remained elusive. Application of electron cryo-microscopy and structural modeling of the bovine endothelial nitric oxide synthase (eNOS) holoenzyme produced detailed models of the intact holoenzyme in the presence and absence of Ca(2+)/calmodulin (CaM). These models accommodate the cross-electron transfer from the reductase in one monomer to the heme in the opposite monomer. The heme domain acts as the anchoring dimeric structure for the entire enzyme molecule, while the FMN domain is activated by CaM to move flexibly to bridge the distance between the reductase and oxygenase domains. Our results indicate that the key regulatory role of CaM involves the stabilization of structural intermediates and precise positioning of the pivot for the FMN domain tethered shuttling motion to accommodate efficient and rapid electron transfer in the homodimer of eNOS.
Keywords: Cattle; Flavin Mononucleotide; Animals; skot; Calmodulin; kalmodulin; hem; Kinetics; Protein Structure, Tertiary; flavinmononukleotid; holoenzymy; Holoenzymes; Electron transfer; terciární struktura proteinů; Three-dimensional reconstruction; vápník; transport elektronů; Nitric oxide synthase; synthasa oxidu dusnatého, typ III; oxidace-redukce; Electron cryomicroscopy; Calcium; Heme; alosterická regulace; Oxidation-Reduction; Image processing; Nitric Oxide Synthase Type III; Allosteric Regulation; zvířata; kinetika; Electron Transport